Designing and evaluating an educational mobile application for prevention of foreign body aspiration and measure to open airways of children - Faezeh Behboudi; Moluk Pouralizadeh; Mohammad Reza Yeganeh; Hossein Khoshrang (Elsevier, 2021)
Background: Foreign bodies aspiration (FBA) in children is one life-threatening event. Education using smartphone applications is an attractive method for reduction of risk and increasing public awareness. The purpose of this study was to design and evaluate an educational smartphone application for parents' education in pre-school age children. Design and Methods.: In this descriptive-developmental study, 25 mothers of pre-school-age children were recruited through cluster random sampling from kindergartens in .... city. Design and evaluation of the application was done in three phases including educational analysis and developing educational content, designing and evaluating the initial algorithms, and designing the final shape. One researcher-made checklist was used to collect the viewpoint of the users. The experts' suggestions were received either by an open ended questionnaire . The viewpoints of users and experts during the design and evaluation process caused some changes in the application. Results: The findings showed a high level of satisfaction among users (4/240 ± 0/96). This application was designed based on the users' needs and based on the feasibility of its usage and the experts' viewpoints about the scientific content, the design and the evaluation stages. Conclusion: The current application can be introduced to the community as an available scientific and user-friendly source which would create a continuous education for public health.